Viver em áreas de riscos: lugar e território de expropriação à jusante da Barragem do Buraco no Sudeste Goiano - Freires, Angélica Silvério (2024)
Mining is an economic activity present in several places in Brazil, whose self-portrait today is the result of the exploration of minerals in the historical course of centuries, which refers to the very process of occupation and organization of the country's territory, in its different temporo-spatial contexts, including the Southeast of Goiás, a spatial section for analysis of the municipalities of Catalão and Ouvidor, with their Niobium and Phosphate. Commonly associated with a practice that generates opportunities, employment, income and foreign exchange, based on the ideological sphere of development and based on aspects such as mining-dependence, public-private partnership, Corporate Social Responsibility, among other aspects, large mining enterprises emerge, which carry out, in a systematic, intensive and domineering way, the use and appropriation of territorial resources. Far beyond the propagated “good practices”, it is necessary to emphasize the Sector’s potential to bring significant changes to human populations and ecosystems in mining municipalities, just as families located in Tailings Dam Self-Rescue Zones are subject. People who even before mining arrived were already established in the place and the technical apparatus puts them at permanent risk. This is the reality experienced by rural communities in Catalão and Ouvidor, in which social conflicts, dam terrorism, topophobia, negative impacts, fear and identity expropriation, with the possibility of physical/geographical exit, define the presence of Mineradora CMOC Brasil for the residents of ZAS of its tailings dam, Barragem do Buraco. At the crossroads of Dam Safety legislation and movements in the territory, attachment to the place confronts the uncertainty of what could happen to these Communities, considering the applicability of the National Dam Safety Policy, which prohibits the presence of people in the ZAS of Tailings Dams. Shaped by documentary research, bibliographic research, observation and fieldwork, with interviews with 30 families living in the ZAS, with Mineradora CMOC Brasil and the State, through the Environmental Departments of the municipalities researched (Catalão and Ouvidor) and the State of Goiás, the Thesis seeks to understand the dynamics associated with the reason for the local human population's permanence in the risk area (ZAS), in the time frame of approximately half a century, from the insertion of this Large Enterprise in the region. Information and communication are a challenge in this context of managing the risk of dam failure. Despite the efforts of the Mining Company to comply with the Dam Safety legislation, it must be stressed that the entire Community needs to be involved in the joint responsibility of ensuring rescue in the event of an emergency. In the search for for non-exposure to “risks and damages”, the families interviewed, who until then feeling insecure, are eager to leave the territory. Another path against self-deterritorialization is dialogue between the Mining Company and the State with the participation of affected communities. It is important that the concerns, needs and expectations of these people are heard, and considered, for the operation of the dam and the Project itself, aiming to guarantee, in fact, the opportunity to choose and exist in the place where they were born, live, work, and where their social relationships and with the environment were primarily topophilic.